Prediction of incident hypertension and arterial stiffness using the non–insulin‐based metabolic score for insulin resistance (METS‐IR) index. Issue 8 (18th July 2019) - Bello‐Chavolla, Omar Yaxmehen; Antonio‐Villa, Neftali E.; Vargas‐Vázquez, Arsenio; Martagón, Alexandro J.; Mehta, Roopa; Arellano‐Campos, Olimpia; Gómez‐Velasco, Donaji V.; Almeda‐Valdés, Paloma; Cruz‐Bautista, Ivette; Melgarejo‐Hernandez, Marco A.; Muñoz‐Hernandez, Liliana; Guillén, Luz E.; et al.
Abstract: Hypertension is associated with insulin resistance (IR), metabolic syndrome (MS), and arterial stiffness. Non–insulin‐based IR indexes were developed as tools for metabolic screening. Here, we aimed to evaluate the novel non–insulin‐based Metabolic Score for IR (METS‐IR) index for the prediction of incident hypertension and arterial stiffness evaluated using pulse wave velocity (PWV) analysis, compared with other non–insulin‐based IR indexes. We evaluated two populations, a cross‐sectional evaluation of high‐risk individuals (n = 305) with a wide range of metabolic comorbidities and dyslipidemia in whom PWV measurement was performed and a 3‐year prospective cohort of normotensive individuals (N = 6850). We observed a positive correlation between METS‐IR and PWV in the cross‐sectional cohort, which was higher compared with other non–insulin‐based fasting IR indexes; furthermore, PWV values >75th percentile were associated with the upper tercile of METS‐IR values. In the prospective cohort, we observed an increased risk for incident hypertension for the upper METS‐IR tercile (METS‐IR ≥ 46.42; HR: 1.81, 95% CI: 1.41‐2.34), adjusted for known cardiovascular risk factors, and observed that METS‐IR had greater increases in the predictive capacity for hypertension along with SBP and the Framingham Hypertension Risk Prediction Model compared with other non–insulin‐based IR indexes. Therefore, METS‐IR is a novel non–insulin‐based IR index which correlates with arterial stiffness and is a predictor of incident hypertension, complementary to previously validated risk prediction models.